Antecedents of Organizational Citizenship Behavior and its Triggering Factors: A Study in A, B & C Category Banking Sector of Hetauda - Mahat, Umesh; K.C., Gautam; Ghimire, Sanjit; Raut, Bin Bahadur; Khatiwada, Purushottam (International Research Journal of MMC, 2023)
Organizations work with the people and for the people. They need employees and the employees need the organizations. It is very important for financial institutions to find out the factors that trigger the exhibition of organizational citizenship behavior. This research is solely undertaken only to identify the status of the employees in Nepalese financial institutions. The aim of the study is to examine and explore the interactions and the direct effects of the independent variable on Organizational Citizenship Behavior, and how this independent variable can encourage this behavior among the workers in their organization. The hypothesis that was required to fulfill the research objectives were derived from the study of the literature. A total of 199 questionnaires were distributed to the potential respondents only 109 respondents were selected out of 397 by using a simple random sampling technique, especially the lottery method in 2022. All the respondents were working individuals of A, B, and C category financial institutions of Hetauda. Data collected from the questionnaire were analyzed and interpreted with the help of different statistical tools; such as means, standard deviations, and frequencies which were used to describe the characteristics of the sample. Cronbach's Alpha was used for the reliability of the instrument used. The descriptive analysis of the independent variable and the dependent variable was conducted and their different dimensions were studied. Pearson Correlation shows that there was a positive correlation between OCB and job satisfaction. The researchers realize the need to enhance job satisfaction in Organization Citizenship behavior for better performance.